2011
DOI: 10.1364/ol.36.001521
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin nickel oxide film as a hole buffer layer to enhance the optoelectronic performance of a polymer light-emitting diode

Abstract: In order to promote a polymer LED (PLED), we fabricated and introduced an ultrathin nickel oxide (NiO) buffer layer (<10 nm) between the indium tin oxide (ITO) anode and the poly (3, 4-ethylenedioxythiophene) hole injection layer in the PLED. The NiO buffer layer was easily formed on the ITO anode by electron-beam deposition of a nickel (Ni) metal source and an oxygen plasma treatment process. As a result, the PLED device with the NiO buffer layer on its ITO anode had the same turn-on voltage as conventional P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Another important application for NiO is the hole‐transporting layer (HTL) in organic optoelectronic or PV devices. Irwin and co‐worker performed an excellent study on the use of NiO for the HTL in organic PV devices .…”
Section: Miscellaneous Applications Of P‐type Oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important application for NiO is the hole‐transporting layer (HTL) in organic optoelectronic or PV devices. Irwin and co‐worker performed an excellent study on the use of NiO for the HTL in organic PV devices .…”
Section: Miscellaneous Applications Of P‐type Oxidesmentioning
confidence: 99%
“…The same mechanism works for light‐emitting diodes (LEDs) or organic LEDs, compared with ITO, a better band alignment between the NiO and the p‐layers can be achieved. It was shown that, the NiO HTL increases both the LED drain current and the luminance, and enhances the power conversion efficiency …”
Section: Miscellaneous Applications Of P‐type Oxidesmentioning
confidence: 99%
“…But, TMOs are usually deposited by vacuum process under 10 −7 Torr and high temperature process is needed to evaporate TMOs, which requires high manufacturing cost. Therefore, vacuum process is not compatible with lost‐cost flexible electronics . On the other hand, solution processing has advantages of low‐cost and simple process, as a result, it is suitable for cost‐effective PLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…, bare ZnO. Since NiO contributes only negligibly to the CL intensity (as seen in Figure 3 ), we can conclude that enhanced defect related luminescence from the composite nanostructure is due to the influence of the p-type NiO on n-type ZnO and can be related to hole injection and simultaneous recombination of electrons and holes [ 43 ].…”
Section: Resultsmentioning
confidence: 99%